Identifying social class differences through speech style analysis in ‘Kingsman: The Secret Service’ - Fiolina Salsabila Maharani; Dwi Wulandari (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2026)
This study aims at analyzing the relationship between speech style and social class in the film Kingsman: The Secret Service (2014). This study employs a qualitative method to analyze the language style of the main characters Eggsy and Harry, who are from the lower social class and upper class, respectively. Through note-taking and thematic analysis, the writer gathered 489 total utterances from both characters. Harry’s speech consists of 226 utterances, and primarily consists of the Consultative style (124 utterances), and all employ standard grammar emblematic of his upper social class. However, Eggsy’s 263 utterances consist of the Casual speech style (153 utterances) the most and include speech that contains non-standard grammar (11 utterances), reflecting his lower social class. Additionally, the study finds that the Function social factor significantly influences both characters’ speech; Harry prioritizes message conveyance and sincerity, while Eggsy’s speech emphasizes self-expression and defense.  The study discovers that the difference in the dominant speech styles is indicative of their social class in the way they employ the speech styles in places and contexts that do not require it.